2019
DOI: 10.5430/ijfr.v10n5p1
|View full text |Cite
|
Sign up to set email alerts
|

Crude Oil Price and Exchange Rates - The Case of Malaysia and Brunei

Abstract: This study is driven by the motivation to investigate the impacts crude oil price fluctuations on Malaysian and Brunei exchange rates as proxied by RM/USD and BD/USD respectively. Even though there is no specific economic theories that can help explain the interaction between commodity and foreign exchange markets, the study is research-worthy as both Malaysia and Brunei are major oil-exporting countries in South East Asia. This study is considered quite extensive involving 370 data points spanning from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Technically, an upsurge in inflation and GDP both decline firms' debt [34]. Visibly, Shariah-tagged firms were considered safe and less effective during the last financial crisis, the recent pandemic, and during different inflation and economic regimes (see [13,31]). Moreover, these firms have more diversification options because they have less systematic risk and are thus able to maintain their earnings during financial crises [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technically, an upsurge in inflation and GDP both decline firms' debt [34]. Visibly, Shariah-tagged firms were considered safe and less effective during the last financial crisis, the recent pandemic, and during different inflation and economic regimes (see [13,31]). Moreover, these firms have more diversification options because they have less systematic risk and are thus able to maintain their earnings during financial crises [56].…”
Section: Discussionmentioning
confidence: 99%
“…The selected dependent and independent variables to perform the analysis with their measurements are displayed in Table 2. The former studies (see [16,31]) indicate that the capital structure of Shariah-tagged firms is a dynamic property. Hence, this observed inquiry has chosen the Panel Data Dynamic model that was previously executed by several investigators (see [2,14]) to discover dynamic relations among the explored variables.…”
Section: Methodsmentioning
confidence: 99%
“…There have been studies that define the relationship between crude oil prices and the exchange rate market, but none of which have shown any theoretical framework regarding the linkage of the two variables (Orzesko, 2021; Hadi et al, 2019). Based on the literature, they have said that there is no economic theory that explains or justifies the nexus between commodities and exchange rates, which is somehow questionable at the same time, interesting.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The author found that there is a long-term cointegration in all the periods, though the short-term impact was found only in 2 quarters from 2016 to 2019. Finally, Hadi et al (2019) analyzed the impact of crude oil prices on the exchange rate of Malaysia and Brunei on the data from 1988 to 2018 by applying Granger causality and a two-step cointegration test. Results indicate a long-term relationship between oil prices in the exchange rate of Brunei and Malaysia.…”
Section: Association Between Oil Prices and Exchange Ratesmentioning
confidence: 99%